2018
DOI: 10.1002/jssc.201701543
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment, dissipation behavior and persistence of quinalphos in/on green pea by gas chromatography with electron capture detector

Abstract: Chemical investigation was carried out to examine the risk assessment, dissipation behavior, persistence, and half-life period of quinalphos in/on green pea fruit by spraying quinalphos at fruiting stage followed by another application after 10-day interval. The samples were extracted by using the quick, easy, cheap, effective, rugged, and safe method, and the residues of quinalphos were analyzed by gas chromatography with electron capture detector. Herein, we report a novel, accurate, and cost-effective gas c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

9
0

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
(21 reference statements)
5
26
0
Order By: Relevance
“…Based on the results, the maximum concentration of ethion residues in cucumber samples was found two hour after pesticide application and its concentration decreased with increasing the storage time. This result is in accordance with other studies on the persistence of ethion residues and the same trend were found in quinalphos and ethion on green pea .…”
Section: Resultssupporting
confidence: 93%
“…Based on the results, the maximum concentration of ethion residues in cucumber samples was found two hour after pesticide application and its concentration decreased with increasing the storage time. This result is in accordance with other studies on the persistence of ethion residues and the same trend were found in quinalphos and ethion on green pea .…”
Section: Resultssupporting
confidence: 93%
“…The degradation kinetics of carbendazim and triazophos residues in green pea was confirmed by comparing residue concentration against time, and the results are depicted in Table 2. The persistence of carbendazim and triazophos residues was expressed in terms of half-life (T 1/2 ) or DT 50 which is 1.27 and 1.82 days ( Table 2) by following first-order kinetics [16,25].…”
Section: Degradation Kinetics and Half-life Of Carbendazim And Triazomentioning
confidence: 99%
“…Therefore, RP‐HPLC appears the helpful approach of choice affording identification, separation and quantification of pesticides . In present communication with continuation of our previous studies on application of chromatography, risk assessment, persistence and simultaneous quantification of carbendazim and triazophos has been evaluated by validated reversed phase high performance liquid chromatography.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, gas chromatography (GC) appears the appropriate choice affording identification, separation and quantification of pesticides. In continuation of our previous studies [19][20][21][22][23][24][25][26][27][28] on application of chromatography for fingerprinting and chromatographic method development to assure quality control of vegetables/fruits/medicinal plants, a validated analytical method has been developed for the simultaneous quantification of eight pesticides ( Fig. 1) from apple: chlorpyrifos-methyl (1), chlorpyrifos (2), quinolphos (3), profenofos (4), myclobutnil (5), ethion (6), fenpropathrin (7) and cypermethrin (8).…”
Section: Introductionmentioning
confidence: 99%